1996
DOI: 10.1055/s-2007-1006625
|View full text |Cite
|
Sign up to set email alerts
|

Long-Segment Nerve Allograft Regeneration in the Sheep Model:Experimental Study and Review of the Literature

Abstract: Experimental work in the field of nerve allotransplantation has dealt with the feasibility of nerve allografts reconstructing nerve gaps. In the majority of studies, the nerve gap studied has been short, and some degree of regeneration has been achieved, even in the untreated allograft. To better approximate clinical nerve-allograft reconstruction, a series of long-segment (8-cm) nerve allografts were performed in the ovine model. Twenty outbred ewes were randomized into two experimental groups with four exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 15 publications
3
51
0
Order By: Relevance
“…1,9,10,13,20 Other authors have failed to demonstrate axonal elongation after cryopreservation of longsegment allografts (8 cm in length). 26 The freeze-thawing process seems to leave perineurial and endoneurial connective tissues intact, effectively preventing infiltration by host lymphocytes as has been observed in fresh allografts and allowing nerve regeneration similar to that observed for autografts, as assessed by qualitative histology. 9 Moreover, experimental studies in rats and primates have demonstrated that immunosuppressive therapies (for example, with tacrolimus or cyclosporine A) maximize axonal regrowth and prevent rejection of the donor nerve 3,12,15,16 when used alone or when combined with allograft pretreatment.…”
Section: Discussionmentioning
confidence: 94%
“…1,9,10,13,20 Other authors have failed to demonstrate axonal elongation after cryopreservation of longsegment allografts (8 cm in length). 26 The freeze-thawing process seems to leave perineurial and endoneurial connective tissues intact, effectively preventing infiltration by host lymphocytes as has been observed in fresh allografts and allowing nerve regeneration similar to that observed for autografts, as assessed by qualitative histology. 9 Moreover, experimental studies in rats and primates have demonstrated that immunosuppressive therapies (for example, with tacrolimus or cyclosporine A) maximize axonal regrowth and prevent rejection of the donor nerve 3,12,15,16 when used alone or when combined with allograft pretreatment.…”
Section: Discussionmentioning
confidence: 94%
“…3,[7][8][9][10][11][12][13][14] Autologous nerve grafts remain the gold standard for repairing longer nerve gaps, but are in limited supply, exhibit donor site morbidity, and may exhibit a size mismatch compared to the transected nerve. Nonautologous grafts can incorporate biological or synthetic components and have been designed with increasing complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Strasberg et al studied an 80-mm nerve allograft in sheep, and Atchabahian et al examined an 80-mm nerve allograft in swine, but both studies showed that axonal regeneration across the untreated allograft was very poor. [18][19][20] Most studies have used short-gaps of <25 mm. [21][22][23][24][25][26][27] Few studies about longer gaps reported poor outcomes similar to allografts.…”
mentioning
confidence: 99%